Measures of Fulfillment of Beliefs for Couples who Memorize the Qur'an from Imam Syafi'i's Perspective in Cepokolimo Village, Pacet District, Mojokerto Regency - Nuroniah, Zuhrufah Jihan; Romli, Muhammad (Majapahit Journal of Islamic Finance and Management, 2024)
Marriage is a way for humans to continue their offspring and preserve their lives. There are rights and obligations in a marriage, namely mutual respect between husband and wife and mutual love. Apart from that, after marriage comes responsibility in the form of maintenance provided by the husband. The most important obligation of a husband is the obligation to provide support, whether in the form of food, clothing, or shelter. Meanwhile, the wife's obligation in a marriage is primarily to obey her husband and maintain her husband's honor. The problem formulation that can be taken from this research is how to measure the fulfillment of livelihood for married couples who memorize the Qur'an in Cepokolimo Village, Pacet District, from Imam Syafi'i's perspective. This research aims to determine the measure of livelihood fulfillment for couples memorizing the Qur'an in Cepokolimo Village, Pacet District, Mojokerto Regency from the perspective of Imam Syafi'i. The research method uses a qualitative approach with a case study type of research and is descriptive. In this research, data collection techniques were carried out using interviews, documentation, and data presentation. Supporting the wife is mandatory for the husband even if the husband does not have a fixed income. In this research, it can be concluded that the implementation of the size of living provided by husbands who memorize the Qur'an from the perspective of Imam Syafi'i in Cepokolimo Village, Pacet District, not everyone is aware of this provision, even though they are among those who memorize the Qur'an, most of them do not understand about it. the size of the living determined by Imam Syafi'i, fulfilling the living for his wife according to her abilities and what she is.